Holisme Sebagai Suatu Upaya Keadilan Ekologis: Kritik Ideologi Terhadap Mazmur 8:1-10 Dan Kolose 1: 15-23 - Aletheia Christo Pattiasina (Sekolah Tinggi Teologi Aletheia, 2025)
Ecological damage resulting from a lack of awareness about the integrity of creation continues to occur in Indonesia, particularly in Maluku. The destruction of nature by non-natural forces is evidence of this reality. The devastation of nature should be a common concern of the church and society. The church should examine texts from an ecotheological perspective, such as Psalm 8:1-10 and Colossians 1:15-23. Therefore, this article aims to reinterpret the two biblical texts through an ideological critique approach. The analysis reveals that the context of each text influences the narrative on ecology and reflects the author's ideology, which has not fully and comprehensively considered the gap between God, humans, and nature. Ultimately, the article highlights the fundamental importance of holistic, whole creation in addressing ecological injustice.